Failed back surgery syndrome treatment using spinal cord stimulation in Lithuania - Vaišvilas , M.; Radžiūnas , A.; Deltuva , V.; Tamašauskas, A. (Neurologijos seminarai, 2018)
Treatment of chronic neuropathic pain is a devastating problem when proper symptom relief is hardly achievable. Many of the treated patients become unable to work because of their disability and face psychosocial problems. Failed Back Surgery Syndrome is defined as persisting chronic neuropathic pain after a successful lumbar spine surgery. Spinal cord stimulation remains a treatment option when modern pain treatment modalities fail. Although such treatment’s efficacy is proved and it is used globally, in Lithuania very few patients had the benefit of such treatment. In this article we describe a 55-year-old male patient, treated for Failed Back Surgery Syndrome using spinal cord stimulation in The Hospital of Lithuanian University of Health Sciences (LSMU) Kauno klinikos.
Keywords: failed back surgery syndrome; chronic neuropathic pain; spinal cord stimulation